2019
DOI: 10.1016/j.ejmg.2018.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of publics who are unwilling to donate DNA data for research

Abstract: With the use of genetic technology, researchers have the potential to inform medical diagnoses and treatment in actionable ways. Accurate variant interpretation is a necessary condition for the utility of genetic technology to unfold. This relies on the ability to access large genomic datasets so that comparisons can be made between variants of interest. This can only be successful if DNA and medical data are donated by large numbers of people to ‘research’, including clinical, non-profit and for-profit resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
110
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(126 citation statements)
references
References 32 publications
12
110
4
Order By: Relevance
“…Participants were classified as willing to donate if they said they would agree to make their data available to at least one of the three groups: medical doctors, non-profit researchers, or for-profit researchers. This proportion is lower than in the English speaking countries where more than 67% were willing to donate their medical and DNA information in at least one scenario [6]. When asked whether they would donate their DNA and medical information for use by medical doctors, almost half of our respondents (48%) said they would; about one quarter (25%) said they would not, and 28% said they were unsure ( Table 3).…”
Section: Willingness To Donate Medical and Genetic Datamentioning
confidence: 73%
See 1 more Smart Citation
“…Participants were classified as willing to donate if they said they would agree to make their data available to at least one of the three groups: medical doctors, non-profit researchers, or for-profit researchers. This proportion is lower than in the English speaking countries where more than 67% were willing to donate their medical and DNA information in at least one scenario [6]. When asked whether they would donate their DNA and medical information for use by medical doctors, almost half of our respondents (48%) said they would; about one quarter (25%) said they would not, and 28% said they were unsure ( Table 3).…”
Section: Willingness To Donate Medical and Genetic Datamentioning
confidence: 73%
“…Producing such empirical evidence on people's views and preferences is the purpose of the "Your DNA, Your Say" (YDYS) study, a collaborative large-scale survey that is currently available in 14 languages. First results from the English-language survey have been published [6,7]. Respondents to the English-language arm were based in four countries: the United Kingdom, the United States, Canada, and Australia.…”
Section: Introductionmentioning
confidence: 99%
“…Our ndings showed that intrapersonal differences might exist between participants and non-participants relating to their considerations on trust in society, and in data repositories, as well as their perceptions about society and research. These ndings therefore provide some support for signi cance of the relationship between trust and willingness to participate in research that is well-established [18,19,23,26,[51][52][53]. Although a lack of trust is associated with high levels of concern and low levels of awareness of current research and data-sharing or data-linking practices [18,19,53,54], our ndings indicate that simply increasing the provision of information on data management or biobanking might indeed not be enough [18].…”
Section: Discussionmentioning
confidence: 59%
“…Speci cally, our ndings show that a lack of engagement in health research practices and inadequate communication of information do not fully explain non-participation in biobanking, as perceptions about society and research appeared to vary between participants and non-participants. Recent quantitative studies conducted on individuals unwilling to contribute to biobanks con rmed that their willingness to participate depended on their perceptions and interest or familiarity in biobanking [18,28]. Moreover, the ndings of a pan-European quantitative study and of a systematic review revealed that a preference for broad or narrow informed consent depended on attitudes towards biobanking research, such as bene ts, concerns, and information needs [19,54].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation